Protection of the myocardium against ischemia/reperfusion injury by punicalagin through an SIRT1-NRF-2-HO-1-dependent mechanism. (1st June 2019) - Yu, Li-Ming; Dong, Xue; Xue, Xiao-Dong; Zhang, Jian; Li, Zhi; Wu, Hong-Jiang; Yang, Zhong-Lu; Yang, Yang; Wang, Hui-Shan
Abstract: Punicalagin has been found to exert cardiac protective effects against myocardial ischemia/reperfusion (MI/R) injury, although the detailed mechanisms remain largely unknown. This experiment was performed to explore the potential involvement of silent information regulator 1 (SIRT1)-NFE2-related factor 2 (NRF-2)-heme oxygenase-1 (HO-1) pathway in the cardiac protective actions of punicalagin. Sprague-Dawley (SD) rats were subjected to MI/R operation with or without punicalagin treatment (40 mg kg −1 d −1 ). We showed that punicalagin-treated group exhibited enhanced cardiac function, reduced myocardial infarction and decreased cleaved caspase-3 level. Furthermore, myocardial oxidative/nitrosative stress was ameliorated by punicalagin as evidenced by suppressed superoxide generation, gp91 phox and iNOS expressions, NO metabolites as well as myocardial nitrotyrosine level. Additionally, punicalagin decreased myocardial IL-6, TNF-α and the levels of ICAM-1, VCAM-1 and IKK-β expressions as well as IκB-α phosphorylation and NF-κB nuclear translocation. However, these effects were abolished by EX527 (5 mg kg −1 d −1, a selective SIRT1 inhibitor). We further found that punicalagin dose-dependently enhanced SIRT1 nuclear distribution and NRF-2-HO-1 signaling. While EX527 treatment not only reduced SIRT1 activity, but also reversed the activation of NRF-2-HO-1 pathway. Collectively, these results revealed that punicalagin reduced cardiac oxidative/nitrosative stress and inflammatory response induced by MI/R operation through SIRT1-mediated activation of NRF-2-HO-1 signaling. Graphical abstract: Image 1 Highlights: Oral treatment with punicalagin reduces MI/R injury. Punicalagin protects against oxidative/nitrosative stress and inflammatory response. Activation of myocardial SIRT1-NRF-2-HO-1 signaling participates in this process.